WILL YOU CARRY THAT WATCH? INVESTIGATING FACTORS THAT AFFECT CONTINUANCE INTENTION OF SMARTWATCHES - Enginkaya Erkent, Ebru; Köse, Şirin Gizem; Özer Çizer, Ece (International Journal of Contemporary Economics and Administrative Sciences, 2021)
The interest in wearable technologies, especially smartwatches rise day by day parallel with technological developments and an increasing need to monitor health. In line with those developments, this study aims to investigate the role of perceived ease of use, perceived usefulness, user satisfaction, healthology in explaining smartwatch continuance intention. In addition, this study investigates the relationships between perceived ease of use, perceived usefulness, healthology and user satisfaction. Questionnaire method was used to gather data from actual smartwatch consumers in Turkey and the data analyzed by utilizing structural equation modeling. Findings demonstrate that the most powerful variable to explain smartwatch continuance intention is perceived usefulness, whereas perceived ease of use contributes to user satisfaction the most. Also, healthology is positively related to both user satisfaction and continuance intention. The results also highlight the importance of continuance intention to increase intention to recommend smartwatches to other people.